Methylene blue-induced Hemolysis in a patient with lidocaine-induced Methemoglobinemia: a case report - Murad Mehmood (23125915) (2025)
Background Methemoglobinemia is an uncommon but potentially life-threatening disorder where hemoglobin iron is oxidized to the ferric state, impairing oxygen transport. Topical anesthetics such as lidocaine can induce methemoglobinemia. Methylene blue (MB) is the first-line antidote, but high doses can oxidize hemoglobin and may precipitate hemolysis even in individuals with normal glucose-6-phosphate dehydrogenase (G6PD) activity. Case Presentation A 31-year-old woman with recurrent genital herpes self-applied excessive 5% lidocaine cream (≈3 tubes/day) for two weeks. She presented with progressive fatigue, cyanosis and hypoxemia. Arterial blood gas showed methemoglobin 13.6%. She received intravenous MB at another hospital and subsequently developed severe anemia (hemoglobin 6.6 g/dL) with laboratory evidence of intravascular hemolysis. G6PD activity was normal. Supportive management included high-flow oxygen, oral ascorbic acid, intravenous antivirals and antibiotics, and transfusion of two units of packed red blood cells. Methemoglobin levels and hemoglobin gradually normalized, and she was discharged in stable condition. Conclusion This case illustrates the paradoxical risk of MB-induced hemolysis in a G6PD-sufficient patient. Clinicians should consider alternative treatments such as ascorbic acid when managing methemoglobinemia and educate the public on safe use of topical anesthetics. Other Information Published in: Oxford Medical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/omcr/omaf264